1947. Influenza Vaccination via Oral Tablet is Protective and Induces a Unique Mucosal Immune Response. (26th November 2018) - Kolhatkar, Nikita; Gottlieb, Keith; Kasparek, Kassandra; Hodgson, Katie; Tucker, Sean; Liebowitz, David
Abstract: Background: Oral vaccines delivered as tablets offer several advantages over traditional injection-based vaccines including ease of distribution and administration as well as temperature-stable formulation options. Oral vaccination is also advantageous because it directly induces a strong mucosal response, which is thought to be critical for preventing future infections. Here we present results from a phase II clinical challenge study comparing efficacy of an oral recombinant adenovirus-based vaccine expressing hemagluttinin (HA) from A/California 04/09 to that of a commercial injectable quadrivalent (QIV) influenza vaccine. Methods: In this 2016–2017 clinical trial (NCT02918006), subjects were immunized with either oral vaccine, QIV, or placebo and then challenged 90 days post-immunization with wildtype influenza A H1 virus to measure vaccine efficacy and durability. Protection was assessed by measuring changes in HAI titres, microneutralization, and IgA/IgG ASC assays. Additionally, exploratory flow cytometry evaluated quantitative and qualitative aspects of immunogenicity including markers of activation and mucosal homing on B cells. Analysis was performed on days 0 and 7 post-immunization and 0 and 6 days post-viral challenge. Plasmablasts sorted from PBMCs were then isolated for genomic DNA and sequenced for heavy chain receptor sequencing using NGS analysis. Results: Of the subjects immunized with Vaxart's oral tablet vaccine, 48% were protected. QIV, by comparison, protected 38% of immunized individuals. Only 37% of Vaxart subjects developed influenza infection compared with 44% of QIV subjects and 71% of placebo subjects. While both vaccines induced a humoral immune response, FACS analysis and NGS revealed that Vaxart subjects had more activated plasmablasts expressing surface mucosal homing markers and a more diverse B cell population than QIV subjects. Conclusion: Vaxart's oral influenza tablet vaccine protected against influenza infection as well or better than injectable QIV. However, the mechanism of protection appears to be unique to the route of immunization; oral immunization allows for specific homing of influenza specific B cells to sites of infection and produces a more diverse antibody repertoire. Disclosures: N. Kolhatkar, Vaxart, Inc.: Employee, Salary. K. Gottlieb, Vaxart, Inc.: Employee, Salary. K. Kasparek, Vaxart, Inc.: Employee, Salary. K. Hodgson, Vaxart, Inc.: Employee, Salary. S. Tucker, Vaxart, Inc: Employee, Salary. D. Liebowitz, Vaxart, Inc.: Employee and Investigator, Salary.